Gender disparities and barriers to access and use of essential health services in Ethiopia: Designing primary health care through gender lens. - Agumasie Semahegn; Yohannes Mehretie Adinew; Gizachew Tadele Tiruneh; Mesele Damte Argaw; Biruhtesfa Bekele; Metadel Tesfaye; Nebreed Fesseha; Samrawit Hagos Tiku; Asmeret Gebrehiwet; Addis Girma; Mebrie Belete; Chala Tesfaye; et al. (PLOS Global Public Health)
Despite remarkable gains in maternal and child health (MCH) outcomes globally, the lack of access to and use of essential health services remains a challenge in low-income countries, like Ethiopia. To address health service access and use, the Ethiopian government has endorsed a fifteen-year "Optimizing Ethiopian Health Extension Program" strategy. This study explored gender barriers to access to and use of MCH services in the primary health care (PHC) setting in Ethiopia. An exploratory qualitative study was conducted in nine districts in Ethiopia. Data were collected using 87 key informants and 134 discussants in 18 Focus Group Discussions. Maximum variation sampling use used to identify participants.. Collected data were coded and gender-related barriers were categorized using the USAID's gender analysis domains. The study enrolled 221 study participants who represented key stakeholders, and 45.7% of them were female. Although Ethiopia adopted and ratified global human rights conventions to protect the legal rights and status of women and children, there are gaps in institutional practices of laws, policies, and regulations. Socio-cultural norms favor men and boys over women and adolescent girls which adversely affect their access to and control over assets and resources. Power and decision-making imbalances between men and women are exacerbated by low men's understanding of MCH needs. Women are not empowered to utilize exempted services. Women's traditional workload in the household during and after pregnancy is prioritized over healthcare. Women face challenges in accessing and use of health services due to socio-cultural norms, beliefs, and implementation gaps within the health system of Ethiopia. It is suggested to work with agrarian and pastoral communities to overcome socio-cultural, knowledge-based gender barriers, and addressing gender gapsthat limit women's access to available health services while institutionalizing and tailoring national gender-integrated policies to improve access to and utilization in the PHC system of Ethiopia.